Tunable broadband terahertz metamaterial absorber based on vanadium dioxide - Guishuang Yang; Fengping Yan; Xuemei Du; Ting Li; Wei Wang; Yuling Lv; Hong Zhou; Yafei Hou (AIP Advances, 2022)
The special electromagnetic properties of metamaterials have contributed to the development of terahertz technology, and terahertz broadband absorbers for various applications have been investigated. The design of metamaterial absorbers with tunability is in a particularly attractive position. In this work, a tunable broadband terahertz metamaterial absorber is proposed based on the phase transition material vanadium dioxide (VO2). The simulation results show that an excellent absorption bandwidth reaches 3.78 THz with the absorptivity over 90% under normal incidence. The absorptivity of the proposed structure can be dynamically tuned from 2.7% to 98.9% by changing the conductivity of VO2, which changes the structure from a perfect reflector to an absorber. An excellent amplitude modulation with the absorptivity is realized. The mechanism of broadband absorption is explored by analyzing the electric field distribution of the absorber based on impedance matching theory. In addition, it also has the advantage of polarization and incident angle insensitivity. The proposed absorber may have a wide range of promising applications in areas such as terahertz imaging, sensing, and detection.